Beispiel Nr: 05
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 1x +3y =9\\ 3x -2y = -6 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 1 x +3 y =9\\ II \qquad 3 x -2 y = -6 \\ \text{I nach x auflösen}\\ 1 x +3 y =9 \\ 1 x +3 y =9 \qquad /-3 y\\ 1 x =9 -3 y \qquad /:1 \\ x =9 -3 y \\ \text{I in II}\\ 3 (9 -3 y ) + -2 y = -6 \\ 27 -9 y -2 y = -6 \qquad / -27 \\ -9 y -2 y = -6 -27 \\ -11 y = -33 \qquad /:\left(-11\right) \\ y = \frac{-33}{-11} \\ y=3 \\ x =9 -3 y \\ x =9 -3 \cdot 3 \\ x=0 \\ L=\{0/3\} \end{array} & \begin{array}{l} I \qquad 1 x +3 y =9\\ II \qquad 3 x -2 y = -6 \\ \text{I nach y auflösen}\\ 1 x +3 y =9 \\ 1 x +3 y =9 \qquad /-1 x\\ 3 y =9 -1x \qquad /:3 \\ y =3 -\frac{1}{3}x \\ \text{I in II}\\ 3x + -2(3 -\frac{1}{3} x ) = -6 \\ -6 +\frac{2}{3} x -2 x = -6 \qquad / -\left(-6\right) \\ +\frac{2}{3} x -2 x = -6 -\left(-6\right) \\ 3\frac{2}{3} x = 0 \qquad /:3\frac{2}{3} \\ x = \frac{0}{3\frac{2}{3}} \\ x=0 \\ y =3 -\frac{1}{3} x \\ y =3 -\frac{1}{3} \cdot 0 \\ y=3 \\ L=\{0/3\} \end{array} \end{array} $